Melanoma of Unknown Primary: Evaluation of the Characteristics, Treatment Strategies, Prognostic Factors in a Monocentric Retrospective Study - Del Fiore, Paolo; Rastrelli, Marco; Dall’Olmo, Luigi; Cavallin, Francesco; Cappellesso, Rocco; Vecchiato, Antonella; Buja, Alessandra; Spina, Romina; Parisi, Alessandro; Mazzarotto, Renzo; Ferrazzi, Beatrice; Grego, Andrea; et al. (Frontiers in Oncology, 2021)
Background Melanoma of unknown primary (MUP), accounts for up to 3% of all melanomas. This study aimed to investigate the characteristics, treatment strategies and prognostic factors of MUP patients, in order to shed some light on the clinical behaviour of this malignancy. Methods All the consecutive patients with a diagnosis of MUP referring to our institutions between 1985 and 2018 were considered in this retrospective cohort study. The records of 173 patients with a suspected diagnosis of MUP were retrospectively evaluated for inclusion in the study. Patient selection was performed according to the Das Gupta criteria and a total of 127 MUP patients were finally included in the study, representing 2.7% of the patients diagnosed with melanoma skin cancer at our institutions during the same study period. A second cohort of all consecutive 417 MKP patients with AJCC stage IIIB-IV, referring tions in the period considered (1985-2018), was included in the study to compare survival between MUP and MKP patients.All the diagnoses were based on histopathologic, cytologic and immunohistochemical examination of the metastases. All tumors were re-staged according to the 2018 American Joint Committee on Cancer (AJCC) 8th Edition. Results Complete lymph node dissection (CLND) was the most common surgical treatment; a worse overall survival in these patients was associated with the number of positive lymph nodes (P=0.01), without significant association with the number of retrieved lymph nodes (P=0.79). Survival rates were lower in patients undergoing chemotherapy (CT) and target therapy (TT), and higher in those receiving immunotherapy (IT).417 Patients with AJCC stage IIIB-IV of Melanoma Known Primary (MKP), were included for the survival comparison with MUP.3-year PFS rates were 54% and 58% in MUP and MKP, respectively (P=0.30); 3-year OS rates were 62% and 70% in MUP and MKP, respectively (P=0.40). Conclusions The most common clinical scenario of our series was a male patient around 59 years with lymph node disease. We report that CLND associated to IT was the best treatment in terms of survival outcome. In the current era of IT and TT for melanoma, new studies have to clarify the impact of novel drugs on MUP.